PROMOTING THE INTERNET IN RURAL AREAS THROUGH TRAINING FOR STUDENTS OF SMA HKBP DOLOK SANGGUL - Martin (Jurnal Prinsip Pengabdian Masyarakat, 2025)
Women, especially housewives, hold a number of central functions in the family and are important economic resources. Empowerment of women is very important because it can create conditions, atmosphere, climate, which allows the potential to develop. The main priority of empowerment is the creation of independence. Self-empowerment efforts have also been realized by groups of housewives who are PKM partners, consisting of three people joined in the "SMA HKBP" and three people from the "SMA HKBP" located in, Dolok Sanggul. The objectives of this PKM activity are: 1) help empower groups of housewives who desire to become entrepreneurs; 2) help PKM partners in creating skills and comfort in community life through entrepreneurship; 3) improve thinking, reading and writing skills or other skills such as internet use. The targets of this program are: 1) the formation of a new business in the field of handicrafts from rope or thread curry (macrame); 2) availability of production support tools to produce creative macramé products; 3) there is an increase in knowledge and skills in producing various types of creative macarame products and are in demand by consumers. The outputs of this program are: Entrepreneurship Module, Basic Financial Accounting Module, and Use of Technology, Information and Communication Module. The implementation method is carried out to achieve the purpose of community service through PKM activities through discussion methods, technical guidance/training, workshops, and mentoring. Through PKM activities, empowering partner groups to become entrepreneurs is expected to help empower groups of housewives who are PKM partners so that they can improve the welfare of families and surrounding communities in a concrete manner .